Determination of wave field properties in the spatial domain from space borne SAR images - Nieto-Borge, Jose Carlos; Niedermeier, Andreas; Lehner, Susanne; Rosenthal, Wolfgang (2003)
New techniques have been developed to study single wave events and wave groupiness from space borne SAR images of the sea surface. These techniques are based on the determination of wave groupiness features from the local wave envelope, estimated by using a two dimensional Hilbert transform, and the analysis of the local variability of the wave height within SAR images. This analysis is carried out on a global scale by using 34,310 SAR images, taken by the European satellite ERS-2. The obtained results are used to generate global maps of maximum wave heights, and other parameters of describing wave events, which are able to inform about potentially dangerous situations for navigation and offshore structures.